Circulating hepcidin in type 2 diabetes: A multivariate analysis and double blind evaluation of metformin effects. Issue 12 (20th October 2015) - Suárez‐Ortegón, Milton Fabián; Moreno, María; Arbeláez, Alejandra; Xifra, Gemma; Mosquera, Mildrey; Moreno‐Navarrete, José María; Aguilar‐de Plata, Cecilia; Esteve, Eduardo; Ricart, Wifredo; Fernández‐Real, José Manuel
Abstract : Scope: Very few studies have evaluated serum hepcidin in patients with type 2 diabetes and they have reported conflicting results. In addition, the effect of antidiabetic drugs on circulating hepcidin has not been explored so far. The aims of the study were to evaluate hepcidin concentrations and hepcidin/ferritin ratio in type 2 diabetes subjects and healthy non‐diabetic controls and to evaluate the effect of metformin on hepcidin concentrations. Methods and results: Study 1: Cross‐sectional multivariate study of 239 non‐diabetic individuals and 65 people with type 2 diabetes. The multivariate analysis included covariates of chronic inflammation, BMI, pharmacological treatment, menopausal status and insulin resistance. Study 2: Randomized, double‐blinded, placebo‐controlled 4‐month trial metformin compared to placebo among 36 type 2 diabetic patients. In both groups diet was controlled by maintaining a hypocaloric intake across the trial. Hepcidin levels were significantly lower in patients with type 2 diabetes than in non‐diabetic individuals either in crude or adjusted regression models ( P <0.05). Hepcidin decreased in both arms of the trial (Placebo, p = 0.004; metformin, p = 0.022). Conclusion: Circulating hepcidin was significantly and independently lower in type 2 diabetes. Metformin treatment is not associated with reductions in hepcidin but hypocaloric diet could be involved.